KEANEKARAGAMAN ARTHROPODA PADA TANAMAN CABAI MERAH DI BAWAH NAUNGAN TANAMAN AREN DI SUMATERA SELATAN - Weri Herlin; Chandra Irsan; Oktaviani Oktaviani; Yulia Pujiastuti; Muhamad Ridho Saputra (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2025)
[ARTHROPOD DIVERSITY IN RED CHILI CULTIVATION UNDER SUGAR PALM SHADE IN SOUTH SUMATRA]. Arthropods are essential components of terrestrial ecosystems, functioning as pollinators, decomposers, herbivores, and natural enemies, and their presence reflects the health of agricultural landscapes. The red chili agroforestry system under sugar palm shading in South Sumatra creates a favorable habitat for arthropod communities through the interaction of canopy cover, microclimate conditions, and plant diversity. This study aimed to analyze the structure, diversity, and ecological roles of arthropod communities associated with chili plants withinthis system. Sampling was conducted systematically across several plots, and collected specimens were identified and analyzed using the Shannon–Wiener diversity index, evenness, and dominance metrics. The results showed that the arthropod community consisted of various orders, with predators forming the dominant guild, followed by pollinators, herbivores, and decomposers. The balanced distribution of individuals among trophic groups indicates a stable community structure, while fluctuations in population density were associated with plant growth stages and seasonal variation. The agroforestry environment of chili plants shaded by sugar palms supports a functionally diverse arthropod community that contributes to maintaining biodiversity and enhancing natural pest regulation. Arthropods in shaded cultivation also experience a more stable microhabitat than those in open fields, allowing for stronger interspecific interactions, including predator–prey dynamics that aid in natural pest suppression. Sustained diversity suggests that agroforestry systems reduce environmental stress on arthropod populations, helping communities function effectively. Therefore, the findings of this study provide an important scientific foundation for developing sustainable agroforestry management strategies that improve ecosystem services and support resilient agricultural production. Full txt pdf